Abrasive waterjet machining studies on Al6061/15%LaPO4 composite. (2021) - Deepthi, T.; Balamurugan, K.; Kalusuraman, G.
Abstract: To the Al6061 matrix composite, the monazite structure Lanthanum Phosphate with a weight ratio of 15% is added as the reinforcement. The machinability characteristics of the stir cast composite is predicted using Abrasive Waterjet Machine. Jet Pressure, Stand-Off Distance, and Cutting Speed are taken as independent parameters. Material Removal Rate, Kerf taper Angle, and Surface Profile Roughness are taken as the dependent responses. The influence of the machining parameters is investigated using the Taguchi's L27 orthogonal array through ANOVA table for both single response and multi responses problems by Gray Relational Approach. From the single response study, the jet pressure has significant impact on material removal and kerf angle whereas, the surface finish depends on the cutting speed. For the multi-response problems, stand-off distance shows the superior influences on the output responses followed by jet pressure and cutting speed.